2014
DOI: 10.1590/s1516-35982014001100004
|View full text |Cite
|
Sign up to set email alerts
|

Digestible lysine levels obtained by two methods of formulation of diets for 22-to-42-day-old broilers

Abstract: -The objective of this study was to evaluate the effect of digestible lysine levels in diets with or without supplementation of industrial amino acids on performance, carcass characteristics and nitrogen excretion in broilers of 22 to 42 days of age. Birds were distributed in a completely randomized experimental design in a 4 × 2 factorial arrangement, with four digestible lysine levels (9.0, 10.0, 11.0 and 12.0 g/kg) and two methods to obtain the lysine levels (variation in the proportion of corn and soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
3
0
0
Order By: Relevance
“…Improved FCR was observed due to higher body weight by addition of L-Lys Sulfate. Results are in line with findings of Oliveira et al (2014) reported that FCR was significantly higher in diets with protein bound Lys as compared to diets with free Lys supplementation. According to results of present study in free Lys sources the L-Lys sulfate had higher feed conversion ratio as compared to L-Lys HCl.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Improved FCR was observed due to higher body weight by addition of L-Lys Sulfate. Results are in line with findings of Oliveira et al (2014) reported that FCR was significantly higher in diets with protein bound Lys as compared to diets with free Lys supplementation. According to results of present study in free Lys sources the L-Lys sulfate had higher feed conversion ratio as compared to L-Lys HCl.…”
Section: Discussionsupporting
confidence: 92%
“…This might be due to that addition of synthetic lysine reduces the high lysine ingredient proportion resulting in reduced feed intake. Results are in according with findings of Oliveira et al (2014) who showed that feed intake was significantly lower in Lys supplementation than protein bound Lys diets. Both synthetic Lys sources (L-Lys HCl and L-Lys sulfate) supplementation had similar feed intake.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation